Primary infectious aneurysm of the femoral tripod - Mazza, Milton; Crestanello, Francisco; Estefan, Alberto; Portos, Ruben; Portos, Milton; Cagno, Carlos (Cirugía del Uruguay, 1974)
During the course of sepsis due to salmonella colerasis, a primar y infections (mycotic) aneurysm appeared in the left femoral tripod. Surgery, consisting of resection of neurysm and interpositioning of vein between the external iliac and the superficial femoral arteries, failed due to hemorrhage. A successful bypass was then performed with synthetic prothesis from primitive iliac to popliteal vein through an obturating opening. Surgical treatment in this disease is difficult and failure frequent.